General Awareness of Diabetes Mellitus among a Hospital Population in Chennai: A Survey (Indian Journal of Public Health Research & Development, 2020)
Aim and Objective: The aim of this study is to assess the awareness of diabetes mellitus and knowledge about the various aspects of diabetes including types, treatment modalities, preventive measures and lifestyle modification in the patient population visiting a Dental Hospital in Chennai.Materials and Method: In this study, a questionnaire was prepared and circulated among the subjects to determine the awareness and to inspect the knowledge about the symptoms, diagnosis and preventive measures about Diabetes mellitus among the people. The study sample comprised of totally 100 subjects, both males and females of age group between 20 and 50 years.Results: According to the survey 52% of the individuals are aware about that diabetes can lead to further complications. 82% of the individuals felt that the diabetes can be controlled by exercise. 19% of individuals have not undergone any confirmatory tests for diabetes. 50% of the individuals were under medication for treatment of diabetes and they experienced side effects while taking those medications. 50% of the individuals who participated in the survey have attended a formal diabetes educational programme and they are aware of diabetes through media,relatives and doctors.
Keywords: Diabetes, Medications, Dietary Habits, Exercise, Blood Glucose level.